Specialized Metabolite Profiling-Based Variations of Watercress Leaves (Nasturtium officinale R.Br.) from Hydroponic and Aquaponic Systems - Ivon Buitrago-Villanueva; Ricardo Barbosa-Cornelio; Ericsson Coy-Barrera (Molecules)
Watercress (Nasturtium officinale), a freshwater aquatic plant in the Brassicaceae family, is characterized by its high content of specialized metabolites, including flavonoids, glucosinolates, and isothiocyanates. Traditionally, commercial cultivation is conducted in submerged beds using river or spring water, often on soil or gravel substrates. However, these methods have significant environmental impacts, such as promoting eutrophication due to excessive fertilizer use and contaminating water sources with pesticides. This study aimed to explore two emerging cultivation strategies, i.e., hydroponics and aquaponics, to grow watercress and evaluate its specialized metabolite content using an untargeted metabolomic approach. The goal was to characterize metabolic profiles, identify component variations, and assess changes in metabolite accumulation at two harvest times. Two culture systems (hydroponic and aquaponic) and two harvest stages (‘baby leaf’ and traditional harvest) were examined. The results revealed 23 key metabolites, predominantly glucosinolates and flavonoids, that significantly influenced the metabolic profile discrimination, with the aquaponic system yielding the highest diversity and relative abundance of metabolites (variable importance in the projection (VIP) > 1). Important condition-related compounds were identified via cross-validation (area under the curve (AUC) > 0.7), including isorhamnetin sophoroside–glucoside and gluconasturtiin at the traditional harvest in the hydroponic system and glucoarabin at the ‘baby leaf’ stage in the aquaponic system. These findings highlight the potential of aquaponic and hydroponic systems as sustainable alternatives for watercress cultivation, offering environmental benefits and enhanced metabolite quality.